2006
DOI: 10.1063/1.2204761
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced flux pinning in Ag-sheathed Bi(Pb)–Sr–Ca–Cu–O superconductors tapes with addition of magnetic nanorod γ-Fe2O3

Abstract: The pinning strength of the Ag-sheathed Bi(Pb)–Sr–Ca–Cu–O tapes with the addition of magnetic nanorod γ-Fe2O3 is studied using the exponent n values obtained from power law current-electric field (I-E) characteristics. The starting composition of the γ-Fe2O3 added samples is Bi1.6Pb0.4Sr2Ca2Cu3O10-(γ-Fe2O3)0.01. The rate of decrease of n values in applied fields for the tapes with nano-γ-Fe2O3 is found lower than the tapes without nano-γ-Fe2O3. This indicates that the pinning strength for the tapes with nano γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…A lower optimal amount (wt%) to optimize J c was observed when the tapes are added with magnetic nanoparticles. The optimal amount of CoFe 2 O 4 addition in this study (0.01 wt%) is similar to that of the cFe 2 O 3 -, Fe 3 O 4 -, NiFe 2 O 4 -and NiO-added tapes [17][18][19][20]. For PbO- [15] and MgO [21]-added tapes, the optimal amount is x = 0.1 wt%.…”
Section: Methodsmentioning
confidence: 82%
“…A lower optimal amount (wt%) to optimize J c was observed when the tapes are added with magnetic nanoparticles. The optimal amount of CoFe 2 O 4 addition in this study (0.01 wt%) is similar to that of the cFe 2 O 3 -, Fe 3 O 4 -, NiFe 2 O 4 -and NiO-added tapes [17][18][19][20]. For PbO- [15] and MgO [21]-added tapes, the optimal amount is x = 0.1 wt%.…”
Section: Methodsmentioning
confidence: 82%
“…However, the reports showed the suppression of T c with Fe substitution (for example [3][4][5]). Addition of nanosized γ -Fe 2 O 3 and Fe 3 O 4 in Bi-Sr-Ca-Cu-O superconductors results in enhanced J c [6,7]. α-Fe 2 O 3 substitution in GdBa 2 Cu 3 O 7−δ also showed enhanced critical current density [8].…”
Section: Introductionmentioning
confidence: 92%
“…However, there are a few reports about the contribution with the doping of M = Fe magnetic ion till now, since the magnetic ions of additions may destroy the superconductor properties of the RE123 bulk. Lau et al observed that the Ag-sheathed Bi(Pb)-Sr-Ca-Cu-O tapes with magnetic nano-powder c-Fe 2 O 3 increase the pining strength [9].…”
Section: Introductionmentioning
confidence: 99%